Intermediate biblical Hebrew grammar : a student's guide to phonology and morphology - Reymond, Eric D. (Atlanta : SBL Press, 2017)
"This grammar is intended for intermediate or advanced students of Hebrew who wish to learn more about the history of the Hebrew language, specifically its phonology and morphology. Reymond focuses on aspects of Hebrew that will encourage a student to better remember the words and their inflection as well as those that will reinforce general principles of the language. Specific examples for memorization are outlined at the end of each chapter. The book also serves as a resource for students wishing to remind themselves of the relative frequency of certain phenomena. The book provides students with a "full" picture of the language's morphology by providing tables of the inflection of individual words for most classes of nouns / adjectives as well as tables that set similar verbal inflections side by side"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Added to collection customer.56279.3 - Master record variable field(s) change: 072
Keywords: Hebrew language -- Phonology; Hebrew language -- Morphology; Hebrew language -- Morphology; Hebrew language -- Phonology; FOREIGN LANGUAGE STUDY / Arabic; Electronic books